DETERMINANTS OF FARMERS’ ADAPTATION TO CLIMATE CHANGE IN SELECTED VILLAGES OF DISTRICT MARDAN - Hussain Khan; Yahya Khan; Khuram Nawaz Sadozai; Muhammad Aslam (`, 2025)
This study was conducted to find out determinants of farmers’ adaptation to climate change in selected villages of District Mardan. Three villages namely Hoti, Taus Banda and Mani Khel of Mardan were purposively selected for the study. The total sample size of 161 households was selected using Yamane formula. Primary data was collected through a pre-tested questionnaire. Data was analysed using SPSS. Descriptive statistics reveals that 48% respondents had acquired education up to secondary level. The results further show that 51% respondents cultivated land in the range of 6-10 Jirab (3-5 Acres). About 93% of the respondents were reported that they observed long term changes in term of climate variables. Similarly, 69% of the respondents reported that they have adapted to the climate change and use various adaptation strategies. These strategies included planting different crop varieties (reported by 69%), adjustment in sowing periods (reported by 78%), changes in irrigation timing (reported by 72%). using improved seeds (reported by 67%), use of chemical fertilizer and pesticides (reported by 70% and 68% respectively). Likewise, the estimates of binary regression analysis reveals that coefficient for household income, untimely rains and drought occurrence had positive and significant effects on adaptation to climate change. The overall model was highly significant as shown by the p-value less than 0.001. The study confirms that respondents in the target area have observed climate change and have made some adaptation to climate change. The study recommends initiatives such as awareness programs should be initiated at farm level to improve farmer’s adaptation capacity and enhance the crop resilience to climate change. Key Words: Adaptation, Binary Logit Model, Crop resilience, adaptation Capacity